Managing Distributed Dynamic Systems with Spatial Grasp Technology - Sapaty, Peter Simon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book describes a novel ideology and supporting information technology for integral management of both civil and defence-orientated large, distributed dynamic systems. The approach is based on a high-level Spatial Grasp Language, SGL, expressing solutions in physical, virtual, executive and combined environments in the form of active self-evolving and self-propagating patterns spatially matching the systems to be created, modified and controlled. The communicating interpreters of SGL can be installed in key system points, which may be in large numbers (up to millions and billions) and represent equipped humans, robots, laptops, smartphones, smart sensors, etc. Operating under gestalt-inspired scenarios in SGL initially injected from any points, these systems can be effectively converted into goal-driven spatial machines (rather than computers asdealing with physical matter too) capable of responding to numerous challenges caused by growing world dynamics in the 21st century. Including numerous practical examples, the book is a valuable resource for system managers and programmers.
Chapter 1 Introduction -- Chapter 2 Some Theoretical Background -- Chapter 3 Spatial Grasp Model -- Chapter 4 SGL Detailed Specification -- Chapter 5 Main Spatial Mechanisms in SGL -- Chapter 6 SGL Networked Interpreter -- Chapter 7 Creation, Activation and Management of a Distributed World -- Chapter 8 Parallel and Distributed Network Operations -- Chapter 9 Solving Social Problems -- Chapter 10 Automated Command and Control -- Chapter 11 Collective Robotics -- Chapter 12 Conclusions.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence